"Coach really knew what I needed and understood me well as a person": Effective communication acts in coach-athlete interactions among Korean Olympic archers - Kim, Y.; Park, I. (International Journal of Environmental Research and Public Health, 2020)
The purpose of this study is to qualitatively explore situations in which athletes perceived communication with their coach to be important and determine the effect of this communication on the athletes. Literature on the communication process in sports emphasizes the distinct characteristics of each sports and its setting. However, previous research has not studied various settings in detail, and archery is yet to be explored. The qualitative process included an in-depth, semi-structured interview with eight Olympic archers. Thematic analysis was used to interpret the data. Athletes perceived communication with coaches to be important during their performance, while dealing with psychological crises, and during their training. Our analysis suggests that, depending on the communicative actions, a coach may positively or negatively impact an athlete`s self-awareness, self-confidence, anxiety, autonomy, and motivation. A noteworthy finding of this study is that archers perceive communication with coaches about the selection and management of equipment as important. This study emphasizes the critical role of an athlete`s communication with the coach in various situations and discusses the theoretical and practical implications in the context of sports performance.